2021 ACC/AHA/SCAI Guideline for Coronary Artery Revascularization: A Report of the American College of Cardiology/American Heart Association Joint Committee on Clinical Practice Guidelines. Issue 3 (9th December 2021) - Lawton, Jennifer S.; Tamis-Holland, Jacqueline E.; Bangalore, Sripal; Bates, Eric R.; Beckie, Theresa M.; Bischoff, James M.; Bittl, John A.; Cohen, Mauricio G.; DiMaio, J. Michael; Don, Creighton W.; Fremes, Stephen E.; Gaudino, Mario F.; et al.
Abstract : Supplemental Digital Content is available in the text.